In silico design of a chimeric aspartic protease for cheese production using parental sequences from 2ASI and 1MPP - Saleem, Shilan S.; Abdul Rahman, Mohd Basyaruddin; Leow, Adam Thean Chor; Muhd Noor, Noor Dina; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Elsevier B.V., 2026)
Aspartic proteases from Rhizomucor miehei (RMP; PDB 2ASI) and Mucor pusillus (MPP; PDB 1MPP) are widely used in cheese production for milk coagulation, but their high thermostability and nonspecific proteolytic activity can cause over-hydrolysis of casein, resulting in bitterness and reduced yields. To overcome these limitations, a chimeric aspartic protease was rationally designed by replacing the second C-terminal region of 2ASI (residues 271–361, 91 residues) with the corresponding fragment from 1MPP, sharing 81.3% sequence identity and 94.5% sequence similarity based on amino acid sequence alignment. This 91-residue replacement introduced 17 substitutions, mostly conservative and semi-conservative, which optimized hydrophobic packing, surface charge, and local flexibility. Notably, the shift of Ile236 from a β-sheet to a loop adjacent to Asp237, together with these substitutions, contributed additionally to improved substrate accessibility and potential catalytic performance. The chimeric protease was evaluated using integrated computational approaches. Structural prediction and validation (AlphaFold2; ERRAT 90.09%; Verify3D 95.36%; Ramachandran 94.7%) confirmed a reliable 3D model. Docking via HADDOCK showed stronger κ-casein binding (chimeric: -2.9; 1MPP: -2.1; 2ASI: −1.1). Molecular dynamics and MM-PBSA analyses over the 30–60 °C range showed that the chimeric protease maintained strong binding affinity at all temperatures, with the highest interaction observed at 30 °C, corresponding to its optimal temperature (ΔG = −60.1 kcal/mol). This indicates enhanced thermolability and potential functional improvement. In contrast, the parental enzymes exhibited their strongest binding at 45 °C (1MPP: −53.01 kcal/mol; 2ASI: −33.9 kcal/mol). These results highlight the promise of chimeric design for fine-tuning milk-clotting efficiency and thermal behavior, with experimental validation pending.